Peptides and peptidoaldehydes as substrates for the Pictet–Spengler reaction. (28th May 2013) - Pulka, Karolina; Slupska, Marta; Puszko, Anna; Misiak, Maria; Wilczek, Marcin; Kozminski, Wiktor; Misicka, Aleksandra
<x xml:space="preserve">Abstract</x> The Pictet–Spengler (PS) reaction was performed with various types of substrates: H‐Trp‐OMe and dipeptides with N‐terminal Trp as arylethylamine components and Z‐protected amino aldehydes and peptidoaldehydes as carbonyl components. We found that the C‐terminal part of Trp derivatives did not have any influence on the stereoselectivity of the reaction and the results are the same for simple esters of Trp and dipeptides. On the contrary, the selectivity of the PS reaction with peptidoaldehydes with L configuration of the C‐terminus residue is totally different from that obtained with simple L‐amino aldehydes. It allows us to obtain cis stereoisomers, which cannot be isolated from the reaction with amino aldehydes. But the utility of the peptidoaldehydes as substrates for the PS reaction is reduced by the side formation of enamides which decrease the yield of cyclization. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd.